Systematic identification of novel regulatory interactions controlling biofilm formation in the bacterium Escherichia coli. Issue 1 (December 2017) - Amores, Gerardo; de las Heras, Aitor; Sanches-Medeiros, Ananda; Elfick, Alistair; Silva-Rocha, Rafael
Abstract Here, we investigated novel interactions of three global regulators of the network that controls biofilm formation in the model bacteriumEscherichia coli using computational network analysis, anin vivo reporter assay and physiological validation experiments. We were able to map critical nodes that govern planktonic to biofilm transition and identify 8 new regulatory interactions for CRP, IHF or Fis responsible for the control of the promoters ofrpoS, rpoE, flhD, fliA, csgD andyeaJ . Additionally, anin vivo promoter reporter assay and motility analysis revealed a key role for IHF as a repressor of cell motility through the control of FliA sigma factor expression. This investigation of first stage and mature biofilm formation indicates that biofilm structure is strongly affected by IHF and Fis, while CRP seems to provide a fine-tuning mechanism. Taken together, the analysis presented here shows the utility of combining computational and experimental approaches to generate a deeper understanding of the biofilm formation process in bacteria.